(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Information is presented on the prevalence, etiology and pathogenesis of trigeminal neuralgia. The clinical picture of classical neuralgia and the features of the course of odontogenic neuralgia of the trigeminal nerve are described. The tactics of a dentist in the treatment of patients suffering from this disease due to pathology of the temporomandibular joint are shown. The main methods of treatment and prospects for their improvement are covered.